Pola Kehadiran Suara Penerjemah Dalam Terjemahan The Rainbow Troops Dari Novel Laskar Pelangi - La Ode Andri; Hayatul Cholsy (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The translator’s voice does not appear explicitly in form of text whic is difficult to identify it’s presence. The research aims to invent the presence of translator’s voice and the pattern of it’s constructed in the text of The Rainbow Troops whic is translated from novel Laskar Pelangi. This research is a descriptive and qualitative reserach whics uses the data gathered from translated text. we focus on the “widening segment narrtive text” in translated version. Through an analysis of technique discursive creation, the widening segment of narrtive text represents the translator’s voice presence. Overall, we find that the translator’s voice presences could be categorized into character category (ibu muslimah, lintang dan pak harfan), non-character category (SD Muhammadiyah dan Sekolah PN), inanimate category (Geografis dan Demografi Sejarah) and entity intrarelation (PN-kemiskinan PN-SD dan SD-Samadikun). Moreover, the the translator’s voice presence through translator’s creativity in producing the new widenign form of text has bridged the gap of context between source text and the foreign reader linguistically and culturally. By this presence the emotion and situation of source text could be caught by foreign readres.